Spinobulbar muscular atrophy combined with atypical hereditary neuropathy with liability to pressure palsy. (February 2018) - Choi, Kyomin; Ahn, So Hyun; Baek, Seol-Hee; Kim, Jun-Soon; Choi, Seok-Jin; Shin, Je-Young; Kim, Sung-Min; Hong, Yoon-Ho; Sung, Jung-Joon
Highlights: This case presented with co-existence of 2 rare genetic neuromuscular disorders Spinobulbar muscular atrophy (SBMA) and hereditary neuropathy with liability to pressure palsy (HNPP). This case presented with phenotypic variability of HNPP. The electrophysiological features and symptoms of HNPP may be more diverse than currently known. Abstract: Spinobulbar muscular atrophy (SBMA) is an X-linked recessive disease, presenting motor weakness and wasting of facial, bulbar and limb muscles. Hereditary neuropathy with liability to pressure palsy (HNPP) is autosomal dominant disorder characterized by recurrent neuropathies at common entrapment sites. We report a case of co-existence of SBMA and atypical HNPP with genetic confirmation of CAG expansion in the androgen receptor (AR) gene and deletion of the peripheral myelin protein 22 (PMP22) gene. A 62-year-old man presented with progressive muscle weakness, fasciculations in upper and lower limbs and dysesthesia predominantly in the distal regions. No family members, including his children, experienced similar symptoms. The electrodiagnostic examination was compatible with demyelinating sensorimotor polyneuropathy. Simultaneous hereditary polyneuropathy and motor neuron disease were suspected and relevant genetic testing was confirmed HNPP and SBMA. This case presented with 2 rare genetic neuromuscular disorders and the atypical HNPP phenotype. This case highlight the importance of detailed patient histories, as well as neurological and electrophysiological examinations for diagnosis of atypical and combination of rare genetic disorders.